Behavior of Chlorpyrifos and 3,5,6-Trichloro-2-Pyridinol (Tcp) in a Sodium-Dodecyl Sulphate-Electrokinetic Soil Washing System - Vidal-Fuentes, J; Vidal-Fuentes, J (Elsevier Ltd, 2023)
Chlorpyrifos (CPF) is widely used around the world as an insecticide to control various insect pests. Numerous studies have shown that CPF and its main metabolite, 3,5,6-trichloropyridinol (TCP) are potential contaminants of soils and water resources. In this work an electro-kinetic soil washing treatment with alternating polarity (EKSW-AP) using the anionic surfactant SDS (4 times CMC) in the washing solution was studied as a possible strategy for CPF remediation in soils. The experiments were performed in two types of soils applying an electric field between the electrodes of 1 V cm−1 during 15 days of operation. The main results of this work showed that SDS does not improve the possibility of mobilization of CPF and TCP in the EKSW-AP treatment, due to the low remaining concentration after its adsorption on soils. In the reference systems, without current application, the recovery of CPF was close to 100% of the added mass whereas in the EKSW-AP systems recoveries reached values near to 80%. Kinetic studies performed in untreated soils revealed only the formation of TCP without any other degradation product. Therefore, EKSW-AP process likely favored the degradation of both compounds CPF and TCP, with the formation of another more polar by-product that was obtained in the collector wells. The results of this study showed that the EKSW-AP with the application of SDS does not significantly alter the physicochemical properties of the soils. © 2023 Elsevier Ltd